Factibilidad del sistema de alcantarillado sanitario de las comunidades calerita baja y diseño de la planta de tratamiento en la descarga ubicada en la comunidad calera Shobol pamba. - Córdova Tamayo, Cristhian Esteban (2016)
Nowadays the country is suffering many problems in the environmental sanitation area, such problems affect the normal development of the human being. This is why the Sanitation Engineering has an important role in solving these problems. Basic sanitation is considered essential in order to improve public health and socioeconomic development, especially in countries where a significant part of its population is affected by water related diseases. This kind of diseases are among the three leading causes of morbidity and death in the Country, mainly affecting human groups that live in settlements that have limitations regarding to health. This limits the possibility of having a dignified life and it reduces significantly productivity. The Calerita Santa Rosa and Baja Calerita communities that belong to the rural parish of San Juan province of Chimborazo are not an exception to this problems, these communities lack of basic sanitary sewer service since their creation. The sewage disposal is carried out through a system of latrines, that are discharged into nearby streams or just outdoors. This investigation aims to provide a sanitary sewer system by covering a 100 percentage of these populations, with a treatment plant located in the community of Shobol Pamba, that consists of a series of filters capable of removing contaminant components that belong to the wastewater. In a way that a good quality of water can be secure prior to its disposal to the river. Among the studies carried out, topographical surveys were developed in the research area, community socioeconomic information was collected through and also information on the population that currently lives in the area of influence. There was also an investigation concerning to the country current standards for the design of sewerage and treatment plants.